Aboriginal and Torres Strait Islander peoples' Quitline use and the Tackling Indigenous Smoking program - Emily Colonna; Christina L Heris; Eden M Barrett; Shavaun Wells; Raglan Maddox (Sax Institute, 2024)
Objective: The Australian Government Tackling Indigenous Smoking (TIS) program aims to reduce tobacco use among Aboriginal and Torres Strait Islander peoples, delivering locally tailored health promotion messages, including promoting the Quitline. We aimed to analyse data on use of the Quitline by Aboriginal and Torres Strait Islander peoples nationally, specifically in TIS and non-TIS areas. Methods: We analysed usage of the Quitline in seven jurisdictions across Australia in areas with and without TIS teams (TIS areas and non-TIS areas respectively) between 2016-2020. Demographic and usage characteristics were quantified. Clients and referrals as a proportion of the current smoking population were calculated for each year, 2016-2020. Results: From 2016-2020, 12 274 Aboriginal and Torres Strait Islander people were clients of the Quitline in included jurisdictions. Most (69%) clients were living in a TIS area. Two-thirds (66.4%) of referrals were from third‑party referrers rather than self-referrals. Overall, between 1.25% and 1.62% of Aboriginal and Torres Strait Islander peoples who currently smoked were clients of Quitline (between 1.15-1.57% in TIS areas and 0.82-0.97% in non-TIS areas). Conclusions: The Quitline provided smoking cessation support to approximately 2500-3000 Aboriginal and Torres Strait Islander clients annually between 2016-2020. Referrals from third parties including Aboriginal and Torres Strait Islander services are an important pathway connecting community members to an evidenced-based cessation support service.